Exchange rate and utilization of free trade agreements: Focus on rules of origin. (July 2017) - Hayakawa, Kazunobu; Kim, Han-Sung; Yoshimi, Taiyo
Highlights: Exchange rates affect utilization of free trade agreement (FTA) schemes. We build a theoretical model that incorporates consideration of rules of origins. We use tariff-line level data on the ASEAN–Korea FTA during the 2007–2011 period. Unexpected depreciation of exporters' currency enhances the FTA utilization. Abstract: Tariff rates under a free trade agreement (FTA) are not necessarily used in the majority of trade, even among members of an FTA. One of the causes of this phenomenon is the presence of rules of origin (RoOs), which require exporters to comply with specific conditions when utilizing an FTA scheme. To consider how RoOs should be designed so that exporters can more robustly use an FTA scheme, this paper investigates the effect of exchange rates on FTA scheme utilization with a focus on RoOs. Exchange rates affect exporters' compliance with RoOs by changing the so-called value-added ratio, which is defined as [1–(Price of imported inputs from non-FTA member countries/Export product price)]. Based on a model of pricing-to-market, we propose that an unexpected depreciation of exporters' currency against importers' currency improves the value-added ratio through a rise in the export product's price, which in turn enhances exporters' utilization of an FTA scheme. We also show strong empirical support for the proposition using the detailed product-level data on FTA scheme utilization in Korea's imports from Association of South East Asian Nations (ASEAN) countries.